Existence of Solutions for Boundary Value Problem of Non-linear Integro-differential Equations of Fractional Order - Kavitha, J.; Sadhasivam, V. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we cultivate the existence theory for the following boundary value problem of fractional integro-differential equations Dα u(t) = f(t,u(t), (φu)(t)), t ∈ [0,T], 1